2013
DOI: 10.5430/ijba.v4n4p26
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transformational Leadership and Organizational Culture in National Oil Corporation of Libya

Abstract: The purpose of the study is to investigate the relationship between transformational leadership and organizational culture in National Oil Corporation of Libya. This research was carried out by measuring the data gathered from the five point likert scale. The Multifactor Leadership Questionnaire (MLQ) was used to measure transformational leadership, while the Organizational Culture Assessment Instrument (OCAI) was used to measure organizational culture. Quantitative survey method was applied and a sample of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
4
13
0
3
Order By: Relevance
“…All this information has given in Table 2. Therefore, as can be seen from Table 3 the participants of oil and gas industry in Libya have pointed out the dominant culture in the oil and gas industry in Libya was hierarchy culture, this result consistent with previous studies by (Twati, 2006;Shurbagi andZahari, 2012a andShurbagi, 2014b). The most organizations take turns at different cultures.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…All this information has given in Table 2. Therefore, as can be seen from Table 3 the participants of oil and gas industry in Libya have pointed out the dominant culture in the oil and gas industry in Libya was hierarchy culture, this result consistent with previous studies by (Twati, 2006;Shurbagi andZahari, 2012a andShurbagi, 2014b). The most organizations take turns at different cultures.…”
Section: Resultssupporting
confidence: 89%
“…Organizational commitment has been researched in various contexts; including (a) Perceived Organizational Support (O'Driscoll and Randall, 1999), (b) Performance Among Guest Workers (Shawa, et al 2003), (c) Job Outcomes (Wasti, 2005), (d) Trust, Innovative Behaviour (Lee, 2008), (e) Organizational Culture and Leadership Style (Lok and Crawford, 1999) and (f) Job Satisfaction (Lim, 2010 andShurbagi andZahari, 2013b). Some of these studies pointed out that organizational commitment have a positive relationship with these variables.…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…His results showed that clan and adhocracy cultures have significant higher levels of job satisfaction as opposed to market and hierarchy cultures. However, Shurbagi and Zahari (2012) found significant positive relationship between all organizational cultures and job satisfaction. Zavyalova and Kucherov (2010) found that organizations with market and hierarchic cultures showed average job satisfaction with scores of 4.0 and 4.7, respectively.…”
Section: Job Satisfaction (Js)mentioning
confidence: 72%